Organization of Mass Vaccine Prevention in the Conditions of a Modern Megapolis - A. V. Starshinin; T. N. Elagina; Yu. B. Novikova; G. N. Gribanovskaya; N. N. Kamynina; O. I. Nechaev (Эпидемиология и вакцинопрофилактика)
Relevance. Thanks to decisions taken at the national level, many countries have managed to significantly increase coverage with preventive vaccination and reduce mortality from vaccine-preventable diseases. However, the COVID-19 pandemic has recaptured the relevance of organizing mass vaccination. Based on the current epidemiological situation, characteristics of the population, peculiar features of infrastructure, available resources in individual country, and individual city, various organizational vaccination solutions have been developed and implemented. The Moscow-based experience of vaccinating against influenza at mobile vaccination sites near the Moscow metro stations in 2016 became the starting point in the development of new organizational forms and technologies for mass vaccination in a megapolis, that have been successfully adapted to the new conditions of the COVID19 pandemic.Aims. is to summarize foreign and Russian (exemplified by Moscow) experience in organizing mass vaccination.Material and methods. The study is based on the publication search results in Google and PubMed. The authors selected materials published in 2017– 2023. The implemented analysis of the long-term dynamics in the influenza incidence in the Russian Federation, the Central Federal District (CFD) and Moscow was based on data of the Federal State Statistical Observation Form No. 2 «Information on infectious and parasitic diseases» for 2013–2019.Results and discussion. The analysis of foreign experience shows that the development and implementation of new forms of mass vaccination cannot become a "standard project". In each region of the world, it is organized with due regard to the local economic, legal, social, medical, organizational and even cultural conditions. Vaccination of the population against influenza at mobile vaccination sites near the Moscow metro stations contributed to a 42.3% decrease in the incidence of influenza (from 24.6 in 2016 to 14.2 per 100,000 population in 2017). In 2019, the incidence of influenza in Moscow was 28.8% lower than the CFD one and 62.2% lower than the Russian rate. The recognized successful experience of deploying mobile vaccination sites near the metro stations has been significantly expanded to control the COVID-19 pandemic with mobile teams, vaccination sites in shopping centers, etc.Conclusion. The conducted research and literature data substantiate the deployment of additional vaccination sites to ensure the necessary coverage with vaccination within a short period of time.